High-Level Disinfection of Otorhinolaryngology Clinical Instruments: An Evaluation of the Efficacy and Cost-effectiveness of Instrument Storage. (January 2018) - Yalamanchi, Pratyusha; Yu, Jason; Chandler, Laura; Mirza, Natasha
Objectives: Despite increasing interest in individual instrument storage, risk of bacterial cross-contamination of otorhinolaryngology clinic instruments has not been assessed. This study is the first to determine the clinical efficacy and cost-effectiveness of standard high-level disinfection and clinic instrument storage. Methods: To assess for cross-contamination, surveillance cultures of otorhinolaryngology clinic instruments subject to standard high-level disinfection and storage were obtained at the start and end of the outpatient clinical workday. Rate of microorganism recovery was compared with cultures of instruments stored in individual peel packs and control cultures of contaminated instruments. Based on historical clinic data, the direct allocation method of cost accounting was used to determine aggregate raw material cost and additional labor hours required to process and restock peel-packed instruments. Results: Among 150 cultures of standard high-level disinfected and co-located clinic instruments, 3 positive bacterial cultures occurred; 100% of control cultures were positive for bacterial species ( P < .001). There was no statistical difference between surveillance cultures obtained before and after the clinic day. While there was also no significant difference in rate of contamination between peel-packed and co-located instruments, peel packing all instruments requires 6250 additional labor hours, and conservative analyses place the cost of individual semicritical instrument storage at 97, 852.50 per year. Discussion: With in vitro inoculation of >200 otorhinolaryngology clinic instruments, this study demonstrates that standard high-level disinfection and storage are equally efficacious to more time-consuming and expensive individual instrument storage protocols, such as peel packing, with regard to bacterial contamination. Implications for Practice: Standard high-level disinfection and storage are equally effective to labor-intensive and costly individual instrument storage protocols.